Burkitt type lymphoma: in predominantly multicentrical digestive presentation. - Perrier, José; Estrugo, Roberto; Navarrete, Héctor; Maedo, Noemi; Atahides, Estela; Furtado, Alejandro (Cirugía del Uruguay, 1985)
A case is presented of a Burkitt type lymphoma In a predominantly digestiva form. lts histology made it exceptional, developing the characteristic aggresivity of this type of tumor and sita.